Determinant Factors Of Work Stress Of Production Workers At National Printing Company - Moh. Samsul Arifin; Susi Arijanti; Betty Rahayu; Fatimah Malini Lubis; Hedrat M. Nure (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Workplace stress is a physical and psychological disruption of employees brought on by an imbalance between their resources and the demands of their jobs. According to findings from early worker research, 14 out of 30 employees reported feeling stressed at work. Negative effects of unmanaged job stress will be felt by both employees and businesses. The aim of this study was to identify the variables linked to production workers' work-related stress. This study has a cross-sectional design and is quantitative in nature. A total of 76 production workers made up the sample size for the data collection, which took place between September-October 2022. Bivariate analysis with the Mann-Whitney test and the Chi-Square test was used to analyze the data. Over 50% of production workers report experiencing work-related stress. Interpersonal conflict (p-value = 0.039), job uncertainty (p-value = 0.022), workload fluctuations (p-value = 0.040), and extracurricular activities (p-value = 0.032) are the four variables that significantly correlate with work stress.